PENGARUH HARI PERDAGANGAN TERHADAP RETURN SAHAM LQ-45 DI BURSA EFEK INDONESIA - Mellysa Maria; Syahyunan Syahyunan (Jurnal Media Informasi Manajemen, 2013)
ABSTRACT The purpose of this research is to obtain empirical evidence about the effect of the trading day on stock return LQ-45 in Indonesia Stock Exchange and the effects of the fourth and fifth Monday about  the lowest of stock returns on Monday. Sampling method in this study use purposive sampling design. The research sample consists of 35 firms that listed in the LQ-45 during August 2011 – July 2012. The analysis method used is descriptive analysis and multiple linear regression with no intercept (multiple regression through the origin) and hypothesis testing using t-statistics (t-test). The results of the study indicate that day trading effects significantly stock returns LQ-45 in Indonesia Stock Exchange or day of the week effect, but the study failed to prove the effect of the fourth and fifth Monday about the the lowest of stock returns on Monday or week-four effect. Keywords: stock return, day of the week effect, four-week effect.